Machinery lubrication and reliability - Sahoo, Trinath (Industrial Press, Inc., 2020)
While it is mostly "behind the scenes," lubrication is used wherever you look-in all types of machines, vehicles, and aircrafts. Its usefulness is everywhere, in every industry, from all types of manufacturing, power, health, petrochemicals, food, paper, and metallurgy to small industries and agriculture. Lubrication is absolutely essential to the world. There is an undeniable link between maintenance strategy and lubrication reliability. Depending on the industry, maintenance costs can represent between 15-60% of the cost of goods produced. Therefore, the reliability of plant and equipment has a significant impact on the profits of any organization. Unfortunately, most problems related to machinery in plants are lubrication-related. To get maximum benefit from advanced maintenance strategies, an understanding of equipment lubrication is a must. That's why this work is invaluable. This book contains everything a maintenance, plant, or industrial professional needs to know about lubrication theory, with vital information on all the critical equipment lubrication requirements. It illustrates how to improve reliability, maximize equipment life, eliminate unscheduled shut downs, and reduce operating costs.
Filterability
Keywords: Lubrication and lubricants.; elektronické knihy; electronic books